Repellent activity and toxicity of the essential oil of Calyptranthes concinna DC. using the model insect Drosophila melanogaster - M. S. Costa; T. S. Freitas; M. A. S. Oliveira; N. J. S. Araujo; S. P. Silva; Z. S. Silveira; N. S. Macêdo; J. C. Andrade-Pinheiro; H. S. Santos; A. M. R. Teixeira; F. A. B. Cunha; Ivo C. Pita Neto; et al. (Brazilian Journal of Botany, 2026)
Insects, belonging to the phylum Arthropoda, play essential roles in ecosystems, play essential roles in ecosystems, such as pollination, pest control, and decomposition. However, some species are vectors of diseases, which makes the development of control methods crucial. The use of synthetic insecticides, although effective, causes serious environmental and health problems. As an alternative, plant essential oils, which are biodegradable and can have repellent and toxic effects on insects, have gained prominence. This study focuses on the species Calyptranthes concinna DC., belonging to the Myrtaceae family, whose repellent and toxicological properties were evaluated using Drosophila melanogaster Meigan (1830) as an experimental model. The botanical material of Calyptranthes concinna was collected from the Private Natural Heritage Reserve in Palmeira-PR, and the essential oil was extracted from the dried leaves by hydrodistillation. The oil, with a yield of 0.26%, was stored for later analysis. The species Drosophila melanogaster was used as a model for toxicity and repellent activity tests. The tests involved fumigation of flies with different doses of oil, evaluation of damage to locomotor capacity and repellency test using filter paper. Data were analyzed statistically using two-way ANOVA. Calyptranthes concinna essential oil demonstrated low toxicity to Drosophila melanogaster , with 100% survival at all concentrations tested over 48 h and deaths that were not statistically significant compared to the water control. Impairment of locomotor capacity was observed only at the highest concentrations (40 µg/mL) after 3 h, and at intermediate concentrations (20 µg/mL) after 6 h, but these effects were equal to the control after 12 h. The repellency test revealed that the essential oil has a significant efficacy, especially at higher concentrations (39 µg/cm 2 ), comparable to the commercial repellent DEET, indicating that C. concinna essential oil is a promising alternative to synthetic repellents. Calyptranthes concinna essential oil has demonstrated potential as a natural repellent, with low toxicity and efficacy comparable to commercial DEET. Compared to studies with other essential oils and similar compounds, C. concinna oil has shown consistent results, suggesting that it may be an effective and environmentally friendly alternative to synthetic repellents. The presence of terpenes in the essential oil may be related to its repellent effect. These results support the use of C. concinna essential oil as a promising natural repellent.